Assessing Constitutive Activity of Extracellular Calcium-Sensing Receptors In Vitro and in Bone - Chang, Wenhan (2010)
Constitutive activity of the extracellular calcium-sensing receptor (CaSR) has been studied in kindreds with the human disorder autosomal dominant hypocalcemia (ADH) and in an animal model called the Nuf mouse. These families generally showed reduced parathyroid hormone (PTH) secretion and excessive renal calcium (Ca(2+)) excretion. Soft tissues calcifications in the kidney and basal ganglia are frequent (10–50% of ADH cases), and there is a single report of skeletal abnormalities in a family resulting in short stature and premature osteoarthritis. In the latter, a causative mechanism could not be determined. The phenotype of the Nuf mouse is one of ectopic calcifications and cataracts in addition to biochemical abnormalities (low serum Ca(2+) and high serum phosphate concentrations). To better understand the role of CaSRs in the control of osteoblastic function, we generated a transgenic mouse model with constitutively active CaSRs in mature osteoblasts. An analysis of the skeletal phenotype of that mouse indicates that strong signaling by CaSRs in this cell lineage induces alterations in the bone homeostasis reflected in mild osteopenia in male and female mice during growth and in adulthood. These studies indicate that this approach can be readily adapted to assess CaSR actions in other cell systems.